2018
DOI: 10.1051/epjconf/201817107001
|View full text |Cite
|
Sign up to set email alerts
|

Polarization in relativistic heavy ion collisions: a theoretical perspective

Abstract: Abstract. We review the theoretical framework for the calculation of particle polarization in relativistic heavy ion collisions within the hydrodynamical model. The covariant decomposition of the mean spin vector is presented and open theoretical issues addressed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…We can see that the shapes of P x sgn(Y ) , P y sgn(Y ) , and P z are in analogy to sin φ p , − cos φ p , and − sin(2φ p ), respectively, as described by Eq. (12). The features of three quantities at two collision energies are quite similar.…”
Section: Numerical Results and Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…We can see that the shapes of P x sgn(Y ) , P y sgn(Y ) , and P z are in analogy to sin φ p , − cos φ p , and − sin(2φ p ), respectively, as described by Eq. (12). The features of three quantities at two collision energies are quite similar.…”
Section: Numerical Results and Discussionmentioning
confidence: 83%
“…The space distribution of the vorticity field can be probed by the local Λ polarization as a function of the azimuthal angle φ p and the rapidity Y in momentum space, which is expected to have harmonic behaviors as in Eq. (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The comprehensive study of global polarization of hyperons and spin alignment of vector mesons can help us to probe the vorticity field [10][11][12][13][14][15] and, from the spin transport aspect, understand particle production mechanisms during hardronization [3]. For those reasons this topic is gaining increasing interest [16][17][18][19][20][21][22], and in particular it is recently demonstrated that the BNL Relativistic Heavy Ion Collider has produced the most vortical fluid with least viscosity [22].…”
Section: Introductionmentioning
confidence: 99%